Recent Work: Cultural Excavations - Sheila Kennedy; Frano Violich (Oz, 1993)
For many people, the relationship of the "product" of architecture to the contents within which it is produced, commissioned, or used ultimately remains unquestioned. Our work in design research concerns itself with a critical inquiry into new surfaces, sites, programs, and materials that may operate as a scaffolding for contemporary logics of production which define our culture's attitudes towards the artifacts which it produces.